Papua New Guinea Public Expenditure and Service Delivery - World Bank (World Bank, Washington, DC, 2018)
This report is the outcome of a study of public spending and service delivery issues in Papua New Guinea (PNG) undertaken as part of the work on the PNG Poverty Assessment. The study itself is the result of a collaborative effort involving several agencies and organizations including the National Research Institute, the National Department of Education, the Department of National Planning and Rural Development (DNPRD), AusAID and the World Bank. The PESD study is undertaken in a challenging economic and social context for PNG with growing concerns about delivery of basic services. The PNG economy has been in a state of recession since the mid-1990s with negative growth in 7 of the last 9 years. The fiscal situation has been compromised by large deficits. Debt-to-GDP ratio has risen to levels where debt servicing is significant claim on total revenues. Poverty levels have been rising. A growing imperative to contain levels of spending has raised significant concerns for maintaining the level of basic services while needs have grown, and it has also raised pertinent questions about how effectively social spending is translating into the actual delivery of services. The study focuses on the education sector though its findings have wider relevance. The problems that plague the education sector have close parallels in other sectors. The report presents some illustrative data for the health sector for which a limited amount of primary information was collected, but the study’s inquiry into conditions promoting or impeding effective service delivery in education has broader relevance for other sectors in PNG, and beyond that for other countries too.